Studentsâ€™ apologizing in Arabic and English: An interlanguage pragmatic case study at an Islamic boarding school in Indonesia - Al-Rawafi, Abdulkhaleq; Sudana, Dadang; Lukmana, Iwa; Syihabuddin, S. (Universitas Pendidikan Indonesia, 2021)
It is hard to select and produce appropriate semantic formulas of apologizing for paying off violation of social norms to restore harmony. It seems that it is even harder to realize such processes of selection and production in a non-native language. The study is of three folds; namely, it examines the realization of the apology strategies by students of a senior Boarding School in Arabic and English as a non-native language, the effects on the contextual factors (external vs. internal) on the studentsâ€™ apologizing, and the pragmatic transfer. The participants were 101 male and 101 female students, recruited to fill in a Discourse Completion Task (DCT), which consisted of eight situations about the flouting of the politeness rules in the context of the Islamic boarding school, by drawing upon the five semantic formulas of apologizing from Blum-Kulka and Olshtain (1983) of Cross-Cultural Study of Speech Act Realization Patterns (CCSARP) for analyzing the data. The findings show that the students used identical semantic formulas in both languages. They prefer to use the â€œexpression of regretâ€ and â€œpromise for forbearanceâ€ strategies. The findings also reveal that the internal and external factors affected the studentsâ€™ selection and production of the apology strategies in both languages. In addition, the studentsâ€™ pragmatic transfer occurred in linguistic areas, namely overgeneralization, inappropriateness, grammatical contrast, and conceptual transfer from L1 to L2, which are categorized into two types, namely, micro-negative transfer and macro-negative transfer. To conclude, these results indicate the studentsâ€™ on-record-negative politeness attitudes towards the offended parties, which are determined by the contextual factors and the studentsâ€™ lack of grammatical competence.